Analysing folk and literary "Bluebeard" fairy-tales - Дмитрієва, Валерія Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Charles Perrault’s tale is the first literary fairytale, which makes use of "curiosity" and "man-killer" motives. Therefore, it can hardly be distinguished from the folk plot.It is necessary to differentiate between folk and literary tales if we analyze the patterns of evolution and reinterpretation of the primary subjects.Folk tale, being based on sustainable national myths, is intended as an explanation of the difference, brought about by the exclusiveness of national character.Literary fairy-tale analysis touches upon the individual rather than the traditional collective creativity. Thus, the article distinguishes between the notions of folk and literary fairy-tale. Still, the ambiguous perception of Charles Perrault’s piece of art reflects the significance of the scientific problem.The article covers historical and ethnographic preconditions of Charles Perrault “Bluebeard” fairy-tale plot formation.  An overview of scholarly perspectives on the problem of folk-tale and literary tale analysis is offered below. Thus the article distinguishes between the notions of folk and literary fairy-tale.